تطبيق النظرية السلوكية في تعليم مهارة الكلام بمعهد الرحمة للبنات مالانج (دراسة الحالة) - Ikke Wulandari (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
The purpose of this research is to: (1) to reveal the application of the behavioral theory in the teaching of speech skills in Boarding school Ar Rahmah Malang for Girls (2) to describe the results of teaching speech skills from the application of the behavioral theory in Boarding school Ar Rahmah Malang for Girls (3) to describe the disadvantages and advantages of the application of behavioral theory in teaching speech skills in Boarding school Ar Rahmah Malang for Girls This type of qualitative research examines the case study method and obtains data from the interview, observation and documentation. The researcher chose data analysis techniques, such as the Miles and Huberman analysis of data classification, data presentation, and summary / conclusion of data. The researcher chose to examine the data on extension of participation and triangulation.The results of the research: 1) The application of the activities of teaching the skill of speech in the behavioral theory at in Boarding school Ar Rahmah Malang for Girls, vary from two types is teaching the skill of speech in the classroom, including: Speak and memorize the Arabic language. And on the outside of them: giving the vocabulary, the conversation after maghrib, and test vocabulary of language, training speech, the implementation of learning activities of the skill of speech in Boarding school Ar Rahmah Malang for Girls in accordance with the theory of behavior. Because there are educational activities inside and outside the classroom, there is repetition, imitation, conservation and punishment. 2) and the results of teaching the skill of speech in the behavioral theory in Boarding school Ar Rahmah Malang for Girls in the classroom suitable for the promotion of the skill of speech. The researcher looked at the results of the conversation article 100% success of 24 student. It is the article of the dialogue 93% success of 30 student. 3) The advantages of applying the behavioral theory in the teaching of the skill of speech in Boarding school Ar Rahmah Malang for Girls suitable for the material of conversation or exchange that need to practice conservation and speak in Arabic. The disadvantages of the application of behavioral theory in the teaching of speech skill in Boarding school Ar Rahmah Malang for Girls there is not the language environment committee on the example language system, fewer applications do not use daily language, fewer penalties that do not use language.